Terapi Tafakkur untuk Meningkatkan Kesejahteraan Psikologis Orang dengan Lupus (Odapus) - Tarsono Tarsono; Nisa Hermawati (Psympathic : Jurnal Ilmiah Psikologi, 2018)
The purpose of this research was to evaluate the effect of tafakkur therapy on psychological well-being on people with odapus. This study used experimental method with a single case design using the variation of type A-B. The participant was a 24-year-old woman with sjorgen odapus from Syamsi Dhuha Foundation. The results showed that there were changes in psychological well-being between before and after attending tafakkur therapy. It touched the aspect of cognition, affection and psychomotor of the subject. The conclusion of the research was tafakkur therapy could affect psychological well-being on individual with odapus. There were also others factors that influence psychological well-being: social support, social economic status, social networks, religiosity, personality, and intensity of attending therapy activities.